Hadith #314 - Sahih Muslim - Yahya (Sahih Muslim)
I asked Abu Salama what was revealed first from the Qur’an. He said:” 0, the shrouded one.” I said: Or” Recite.” Jabir said: I am narrating to you what was narrated to us by the Messenger of Allah (ﷺ). He said: I stayed in Hira’ for one month and when my stay was completed, I come down and went into the heart of the valley. Somebody called me aloud. I looked in front of me, behind me, on the right of my side and on my left, but I did not see any body. I was again called and I looke
Grade: Sahih

Hadith #315 - Sahih Muslim - Yahya (Sahih Muslim)
And there he was sitting on the Throne between the heaven and the earth.
Grade: Sahih

Hadith #756 - Sahih Muslim - Yahya (Sahih Muslim)
I heard the Messenger of Allah (ﷺ) saying The Mu’adhdhins will have the longest necks on the Day of Resurrection.
Grade: Sahih

Hadith #1320 - Sahih Muslim - Yahya (Sahih Muslim)
They (the enemies) have diverted us from the middle prayer till the sun set. May Allah fill their graves and their houses with fire, or their graves and stomachs with fire.
Grade: Sahih

Hadith #1468 - Sahih Muslim - Yahya (Sahih Muslim)
I told ‘Umar b. al-Khattab that Allah had said:” You may shorten the prayer only if you fear that those who are unbelievers may afflict you” (Qur’an, iv. 101), whereas the people are now safe. He replied: I wondered about it in the same way as you wonder about it, so I asked the Messenger of Allah (ﷺ) about it and he said: It is an act of charity which Allah has done to you, so accept His charity.
Grade: Sahih

Hadith #1478 - Sahih Muslim - Yahya (Sahih Muslim)
I asked Anas b. Malik about shortening of prayer. He said: When the Messenger of’ Allah (ﷺ) had covered a distance of three miles or three farsakh (Shu’ba, one of the narrators, had some doubt about it) he observed two rak’ahs.
Grade: Sahih

Hadith #1483 - Sahih Muslim - Yahya (Sahih Muslim)
I heard Anas b. Malik say: We went out for Pilgrimage from Medina. The rest is the same.
Grade: Sahih

Hadith #2614 - Sahih Muslim - Yahya (Sahih Muslim)
I and ‘Abdullah b. Yazid set out till we came to Abu Salama. We sent a messenger to him (in his house in order to inform him about our arrival) and he came to us. There was a mosque near the door of his house, and we were in that mosque, till he came out to us. He said: If you like you may enter (the house) and, if you like, you may sit here (in the mosque). We said: We would rather sit here and (you) relate to us. He (Yahya) then narrated that ‘Abdullah b Amr b. al-‘As (Allah be pleased w
Grade: Sahih

Hadith #3255 - Sahih Muslim - Yahya (Sahih Muslim)
I said to Abu Salih: Did you hear Abu Huraira (Allah be pleased with him) making a mention of the excellence of prayer in the mosque of Allah’s Messenger (ﷺ)? He said: No (I did not hear directly from Abu Huraira), but I heard Abdullah b. Ibrahlm b. Qariz; say that’ he had heard from Abu Huraira (Allah be pleased with him) that Allah’s Messenger (ﷺ) had said: Prayer in this mosque of mine is better than a thousand prayers. or. is like one thousand prayers observed in other mosques besi
Grade: Sahih

Hadith #3753 - Sahih Muslim - Yahya (Sahih Muslim)
‘Ariyya implies that date-palm trees should be donated to the people and then they sell it with a measure of dry dates.
Grade: Sahih

Hadith #4625 - Sahih Muslim - Yahya (Sahih Muslim)
If a slave is appointed over you and he conducts your affairs according to the Book of Allah, you should listen to him and obeey (his orders).
Grade: Sahih

Hadith #4629 - Sahih Muslim - Yahya (Sahih Muslim)
I heard her say: I performed Hajjat-ul-Wada’ in the company of the Messenger of Allah (ﷺ). He said a lot of things (on this occasion). Then I heard him say: If a maimed slave is appointed a commander over you the narrator says: I think she said:” a black stave” who leads you according to the Book of Allah, then listen to him and obey him.
Grade: Sahih

Hadith #5093 - Sahih Muslim - Yahya (Sahih Muslim)
Are you Muslims? They said, Yes. Thereupon he said: Its sale and purchase and its trade are not permissible. They then asked him about Nabidh and he said: Allah’s Messenger (ﷺ) went out on a journey and then came back and some persons amongst his Companions prepared Nabidh for him in green pitcher, hollow stump and gourd. He commanded it to be thrown away, and it was done accordingly. He then ordered them (to prepare it.) in a waterskin and it was prepared in that by steeping raisins in wate
Grade: Sahih

Hadith #7376 - Sahih Muslim - Yahya (Sahih Muslim)
‘It is enough of a lie for a man that he narrates everything he hears’.
Grade: Sahih

Hadith #7380 - Sahih Muslim - Yahya (Sahih Muslim)
‘Iyās bin Mu’āwiyah asked me saying: ‘Indeed I see that you love knowledge of the Qur’ān, so recite for me a Sūrah and explain it until I can reflect on what you know’. said to me: ‘Memorize from me what I am about to say to you- Beware of abominations in Ḥadīth for indeed rarely does anyone convey them except he lowers himself and his Ḥadīth are denied’.’
Grade: Sahih